THOMAS JEFFERSON AND GUS DUR ON DEMOCRACY, WHY NOT? - Didik Murwantono (Universitas Stikubank (UNISBANK) Semarang, 2010)
This paper discusses some important issues concerning how to give the meanings of democracy in line with the changing of era and models of democracy. It explores some characteristics of two figures: Thomas Jefferson and Gus Dur of Indonesia, characteristics of democracy, and comparison of their ideas about democracy. Thus, it focuses on some ideas of democracy between Thomas Jefferson and Gus Dur whose position as two figures of democracy. It also examines how far the impact of their great ideas in the development of democracy in their own countries, Indonesia and America. The historical, philosophical, political, sociological, and cultural aspects of Jefferson and Gus Dur on democracy will be systematically discussed. In addition to that, it also discusses the description of democracy, the background of American and Indonesian democracy, Jefferson’s and Gus Dur’s concepts of demoracy and some other related issues to democracy. Key words : Thomas Jefferson, Gus Dur, democracy, interdisciplinary approach, liberalism